2017
DOI: 10.2196/jmir.7896
|View full text |Cite
|
Sign up to set email alerts
|

Components and Outcomes of Internet-Based Interventions for Caregivers of Older Adults: Systematic Review

Abstract: BackgroundWhen trying to access interventions to improve their well-being and quality of life, family caregivers face many challenges. Internet-based interventions provide new and accessible opportunities to remotely support them and can contribute to reducing their burden. However, little is known about the link existing between the components, the use of behavior change techniques, and the outcomes of these Internet-based interventions.ObjectiveThis study aimed to provide an update on the best available evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 75 publications
5
86
0
Order By: Relevance
“…Internet-based interventions for informal carers of dementia patients helped to reduce carer burden and improve QoL. 28,29 Ultimately, based on the results of this study, it appears carers who were contacted by trained oncology nurses and were made aware of resources available to them initially lowered their valuation of their QoL and sought available health care services. However, it is logical that over a longer time period, this carer group would see their QoL improved, and potentially utilise fewer health care resources, compared with carers who were not made aware of resources who subsequently indirectly allowed any potential health issues to remain and perhaps even manifest more severely.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Internet-based interventions for informal carers of dementia patients helped to reduce carer burden and improve QoL. 28,29 Ultimately, based on the results of this study, it appears carers who were contacted by trained oncology nurses and were made aware of resources available to them initially lowered their valuation of their QoL and sought available health care services. However, it is logical that over a longer time period, this carer group would see their QoL improved, and potentially utilise fewer health care resources, compared with carers who were not made aware of resources who subsequently indirectly allowed any potential health issues to remain and perhaps even manifest more severely.…”
Section: Discussionmentioning
confidence: 93%
“…The reasoning behind this is unclear, but it may be that discussing carer burden and other issues may make the carers more aware of existing ill health within the timeframe of this study, and therefore possibly assess their QoL as being lower. However, there is some previous research that suggested QoL was negatively impacted due to carer burden, and other research to suggest similar Internet‐based interventions for informal carers of dementia patients helped to reduce carer burden and improve QoL …”
Section: Discussionmentioning
confidence: 99%
“…Supporting caregivers with e.g. stress management may help them deal more constructively with stress, with subsequent positive effects on psychological well-being (Guay et al 2017). Lack of resources and energy, transportation issues and stigma can however be barriers to accessing help, which is why online interventions may be of value to increase accessibility to effective interventions.…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…The focus of the review on carers of people with psychosis is a strength and joins other reviews focusing on technology in different carer populations such as older adults 63 and severe mental illnesses. 64 The review, however, does have some limitations.…”
Section: Limitationsmentioning
confidence: 99%